'Better safe than sorry': examining trauma as an obstacle to empowerment and social change in a U.S. intimate partner violence intervention. Issue 2 (4th March 2022) - Kogen, Lauren
ABSTRACT: Communication for social change (CSC) research often addresses 'empowerment.' This paper argues that CSC must better incorporate trauma healing into the concept of empowerment, and thus into a revised model of social change. Data from a U.S. intimate partner violence intervention are used to provide evidence for the validity of, and usefulness of, such a revised model. Three broad theoretical arguments are offered regarding trauma within CSC: (1) trauma is rarely addressed outside peacebuilding interventions, but is relevant to other marginalized populations; (2) storytelling work has mostly focused on its politically empowering effects, and insufficiently on its healing effects related to trauma as a precursor to political empowerment; and (3) storytelling work almost always assumes an audience, but there is also value in internal communication – e.g. telling a story to oneself or journaling – when trauma has limited one's opportunities for communication.